2007
DOI: 10.4141/p06-150
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and environmental variation in grain, flour, dough and bread-making characteristics of Western Canadian Spring Wheat

Abstract: . 2007. Genotypic and environmental variation in grain, flour, dough and bread-making characteristics of western Canadian spring wheat. Can. J. Plant Sci. 87: 679-690. Wheat (Triticum aestivum L.) grain, flour, dough and bread quality characteristics are strongly influenced by growing-season weather conditions. Understanding the impact of genotype, environment, and their interactions on Canadian wheat quality is important for Canada to maintain its high standard for delivery of consistent quality wheat to dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 31 publications
7
36
0
1
Order By: Relevance
“…This near negligible genotype by environment (G x E) interaction is similar to other published results. Finlay et al (2007) tested six spring wheat cultivars at five locations across Manitoba and Saskatchewan over two years to examine genotypic and environmental variation in grain, flour, dough and bread-making characteristics. They reported that the relative magnitude of the environmental contribution to wheat variance, depending on the trait (including yield), was considerably larger (14 to 89%) than the variance contribution of either genotype (0 to 33%) or G x E interaction (0 to 17%).…”
Section: Resultsmentioning
confidence: 99%
“…This near negligible genotype by environment (G x E) interaction is similar to other published results. Finlay et al (2007) tested six spring wheat cultivars at five locations across Manitoba and Saskatchewan over two years to examine genotypic and environmental variation in grain, flour, dough and bread-making characteristics. They reported that the relative magnitude of the environmental contribution to wheat variance, depending on the trait (including yield), was considerably larger (14 to 89%) than the variance contribution of either genotype (0 to 33%) or G x E interaction (0 to 17%).…”
Section: Resultsmentioning
confidence: 99%
“…The Saskatchewan sites were located at Agriculture and Agri-Food Canada (AAFC) research facilities and the Manitoba sites were located at the University of Manitoba's agricultural research facilities. A more detailed description of the sites can be found in Finlay et al (2007), Gervais (2008) and Mkhabela et al (2010).…”
Section: Materials and Methods Site Location And Descriptionmentioning
confidence: 99%
“…Quality is a complex characteristic and the degree of influence of each component determining its expression is affected by the genotype's behavior to a specific environment. Diverse studies point out that climatic conditions during the growing season, especially during the wheat's reproductive period, are very important since they are closely related to the formation and accumulation of protein reserves (Gaido and Dubois, 2008) that have an impact on genotype quality (Finlay et al, 2007). Borghi et al (1995) point out that in a Mediterranean-type climate, such as the one found in Chile, the G×E interaction has a strong influence and causes important variety response variability for both yield and quality in each season and each planting site.…”
Section: Qualitymentioning
confidence: 99%